Systematics and cuttings rooting performance of cempaka (Magnolia spp.plum. ex L., Magnoliaceae) in Peninsular Malaysia - Hoong, Tan Sin (2020)
Magnolia Plum. ex L. (Magnoliaceae) is a genus of medicinal ornamental trees and shrubs with around 300 species. In Peninsular Malaysia, four species are cultivated while 15 species are wild. Propagation of Magnolia is generally difficult due to seed dormancy and slow rooting. In study of rooting performance of Magnolia champaca, the effects of types of cutting (softwood, semihardwood) and indole-3-butyric acid (IBA) concentrations (0, 6000, 12000, 18000 mg/L) were investigated. Significant differences were found among the types of cutting and IBA concentrations. Almost all semi-hardwood cuttings failed to root. For the softwood cuttings, significant differences in rooting percentage and length of root were found, but not for number of roots. Cuttings treated with 12000 mg/L IBA produced the highest rooting percentage of 66.7% and longest mean length of roots at 7.5 cm, but the treatment is not significantly different with other IBA concentrations used. In the experiment involving M. alba, the effect of ethephon treatments (0, 1 day) and IBA concentrations (0, 3000, 6000, 9000 mg/L) were tested on softwood cuttings. The treatments were not significantly different. Rooting percentage of 40% was obtained in cuttings treated with 9000 mg/L IBA regardless of the ethephon treatment, however, its effect is not significantly different from the others. Histological study on softwood cuttings of M. alba found that root primordia originated from between secondary phloem and callus. Twenty-nine individual trees representative of 5 wild Magnolia species from the forests of Peninsular Malaysia were documented morphologically, mapped and accessioned. The species found are identified as M. elegans, M. liliifera, M. macklottii var. beccariana, M. praecalva and M. villosa. Propagation trials successfully collected 3 accessions of 2 wild species and 2 additional taxa cultivated in Thailand as rooted cuttings. Accordingly, ex situ collection of M. liliifera and M. villosa were successfully made. Forty-two ISSR markers were screened and consequently 25 markers were selected to study 26 Magnolia accessions, which produced 223 bands with 100% polymorphism. Dendrogram generated showed similar relationships with previous studies based on chloroplast DNA sequences. The number of ISSR markers informative for discrimination of infraspecific variation in M. champaca, M. alba, M. macklottii var. beccariana, M. liliifera and M. villosa studied are 12, 13, 21, 25 and 23 respectively. Species-specific bands were found in M. alba (primer UBC807), M. champaca (UBC817), M. macklottii var. beccariana, (primers UBC815, UBC827, i2 and ISSR-B) and M. villosa (primer UBC855) In conclusion, rooting performance of cuttings was investigated using M. champaca and M. alba and the cutting method was applied to collect new germplasm of wild native Magnolia. The documentation process of magnolias discovered new morphological variation and showed that there could be new findings based on observation of living plant in the forest. Protocols for elucidation of Magnolia genetic diversity, molecular identification and genetic relationship developed will be useful for future study and management of these valuable plants.